The planet in a pebble : a journey into Earth's deep history - Zalasiewicz, J. A. (Oxford University Press, 2010)
This is the story of a single pebble. It is just a normal pebble, as you might pick up on holiday - on a beach in Wales, say. Its history, though, carries us into abyssal depths of time, and across the farthest reaches of space. This is a narrative of the Earth's long and dramatic history, as gleaned from a single pebble. It begins as the pebble-particles form amid unimaginable violence in distal realms of the Universe, in the Big Bang and in supernova explosions and continues amid the construction of the Solar System. Jan Zalasiewicz shows the almost incredible complexity present in such a sm.